Cell-Based Microarrays Review of Applications, Developments and Technological Advances - Palmer, Ella (SpringerBriefs in Cell Biology, 2014)
This book is a review on the evolution of cell-based microarrays and an update to the author's earlier book Methods in Molecular Biology: Cell-Based Microarrays. Since their development in 2001, cell-based microarrays have advanced signiﬁcantly to include expression arrays, short interfering RNA arrays and antibody arrays. The surface used to coat the glass slides has also been significantly improved to allow non-adherent cells to bind to the arrays.